2011
DOI: 10.3109/0886022x.2011.586480
|View full text |Cite
|
Sign up to set email alerts
|

Is There Differences in Cognitive and Motor Functioning between Hemodialysis and Peritoneal Dialysis Patients?

Abstract: Objective: Change in cognitive function is one of the well-known consequences of the end-stage renal disease (ESRD). The aim of this study was to determine the effect of hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) on cognitive and motor functions. Methods: In this cross-sectional study, cognitive and motor functions were investigated in a selected population of 42 patients with ESRD (22 patients on chronic HD and 20 patients on CAPD, aged 50.31 ± 11.07 years). Assessment of cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
1
21
1
2
Order By: Relevance
“…However, our study showed no differences in general CI and the major cognitive domains between case-matched PD and HD patients. This is different from the previous studies, which have indicated that the prevalence of general CI is lower in PD than in HD patients [9,10]. One study reported the comparable rates of CI between HD and PD but PD patients have more severe impairment in immediate memory and less impairment in executive dysfunction than HD patients [3].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, our study showed no differences in general CI and the major cognitive domains between case-matched PD and HD patients. This is different from the previous studies, which have indicated that the prevalence of general CI is lower in PD than in HD patients [9,10]. One study reported the comparable rates of CI between HD and PD but PD patients have more severe impairment in immediate memory and less impairment in executive dysfunction than HD patients [3].…”
Section: Discussioncontrasting
confidence: 56%
“…Also, magnetic resonance imaging (MRI) of the brain showed that structural neuroimaging abnormalities such as white matter hyperintensity (WMH), brain atrophy, and overt or silent cerebral infarction is prevalent among HD [5,6] or PD patients [7,8], as compared to healthy or CKD controls. However, a few studies have explored the influence of dialysis modality on the prevalence of CI [3,9,10] , or on the prevalence of structural and functional neuroimaging abnormalities [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Both impaired cognitive function (33)(34)(35) and reduced physical performance measures (2,20,36) have been previously reported in patients established on PD. However, previous studies have not included data regarding functional independence.…”
Section: Discussionmentioning
confidence: 99%
“…We selected these four tests from the CRD series because a strong correlation was found between the results on CRD-series tests and cognitive and psychomotor functions in previous studies with repeated-measures design [19,20,21,22]. The goal was to complete each test as quickly and with as few errors as possible.…”
Section: Methodsmentioning
confidence: 99%
“…The test procedure is noted online and guarantees unbiased documentation. In earlier studies, CRD-series was able to detect even the slightest cognitive and psychomotor changes [18,19,20,21,22,23]. …”
Section: Methodsmentioning
confidence: 99%